2022
DOI: 10.1111/ecc.13638
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in self‐management of persons living with advanced cancer: An exploratory, in‐depth interview study

Abstract: Objective: To obtain insight in self-management challenges of persons with advanced cancer and factors that influence their self-management.Methods: Exploratory study among persons with advanced cancer. We conducted in-depth interviews and performed an inductive thematic analysis, using open, axial and selective coding.Results: We interviewed 33 persons with advanced cancer. Four self-management challenges were identified: (1) Dealing with physical and psychological symptoms and problems. (2) Navigating the il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Interviewers also took field notes. Additional information on the research team and reflexivity of the original study is reported elsewhere 19 . After the interviews, participants completed a questionnaire on demographic characteristics (e.g., type of cancer, year of diagnosis, and current treatment).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interviewers also took field notes. Additional information on the research team and reflexivity of the original study is reported elsewhere 19 . After the interviews, participants completed a questionnaire on demographic characteristics (e.g., type of cancer, year of diagnosis, and current treatment).…”
Section: Methodsmentioning
confidence: 99%
“…The present explorative study is nested in a qualitative study in which in‐depth interviews were conducted with patients with advanced cancer and their relatives, to gain understanding of their challenges in self‐management 19 . Both studies adhere to the COREQ (COnsolidated criteria for REporting Qualitative research) Checklist for qualitative research 20 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to training and education of healthcare professionals to provide high-quality palliative care to patients with incurable cancer and their family caregivers, it also seems beneficial to equip patients and family caregivers themselves. In this issue, Noorlandt et al interviewed 33 patients with advanced cancer about their self-management challenges and showed that many of the challenges occur outside the professional care setting, underscoring the importance of broadening the scope beyond the care setting (Noorlandt et al, 2022). One of these challenges may be work-related.…”
Section: How Can We Overcome These Barriers?mentioning
confidence: 99%